COMPARATIVE STUDY OF TABOO FOOD WORDS IN KOREAN AND MONGOLIAN - KIM, Ki-Sun; LEE, Jong-Oh (Acta Mongolica, 2015)
Taboo words and phrases related to food etiquette in Korea and Mongolia contain the aggregated wisdom and experiences of peoples with histories of overcoming adversity in given natural environments. Unlike proverbs, taboo words and phrases are linguistically straightforward, part of what people believe and use in their everyday life. Thus, in Korea and Mongolia, two countries the comparison of which shows a contrast between settled and nomadic cultures, the expression in language of taboos related to food habits is different in accordance with customs around sex, religion, politics, and other socio cultural differences.